Dampak Usia, Struktur Keluarga, dan Tingkat Pendidikan Terhadap Perilaku Konsumen (Pengunjung) Destinasi Wisata di Kabupaten Tangerang - Ahmad Khusaeni; Khusaini Khusaini; Aniek Widiarti (Universitas Negeri Padang, 2021)
One of the important issues as a generator of the world economy is the tourism sector. It can reflected in fluctuations in the number of visitors to tourist destinations that tend to increase, so it becomes a discussion material by both researchers and policy makers. This study investigate the determinants of consumer behavior in determining tourist destinations in Tangerang Regency, namely age, family structure, and education level. This study used a cross-sectional survey approach and analyzed it with a binary probit regression model. Sample sizes were 395 respondents from an infinite population. The sampling technique used an accidental sampling technique. The primary data was obtained using questionnaires that had been tested for validity and reliability. Probit regression analysis showed that the age and level of education have a significant effect on consumer behaviour (visitors) in the selection of tourist destinations, while the family structure was not significant. The contribution of this research provides an alternative model of analysis and improves the consistency of the results of previous research. The current study also contributed to the importance of managing tourist destinations, in order to provide greater benefits for visitors and increased regional revenues from the retribution.